Effects of water atmosphere on chemical degradation of PrBa0.5Sr0.5Co1.5Fe0.5O5+δ electrodes. Issue 6 (15th March 2021) - Choi, Mingi; Kim, Seo Ju; Lee, Wonyoung
Abstract: Protonic ceramic fuel cells (PCFC) based on a state-of-the-art electrolyte and cathode materials with extremely low ohmic resistance and high surface exchange rate in the intermediate temperature range (500–650 °C) have demonstrated exceptional power output in recent studies. However, reliable long-term operation remains a challenging issue in the development of PCFCs for practical applications. In particular, the water generated at the cathode has been reported to accelerate cation segregation and phase destruction of materials, thereby resulting in significant performance degradation. In this study, we investigate the underlying mechanism of the rapid chemical and electrochemical degradation of thin film PrBa0.5 Sr0.5 Co1.5 Fe0.5 O5+δ model electrodes in a water atmosphere. The electrochemical degradation, concurrent with the formation of Ba- and Sr-enriched surface clusters, was more significant in the water atmosphere than a dry atmosphere. Water adsorption onto the electrode surface was found to substantially alter the chemical states of the electrodes. In particular, the increased oxygen vacancies caused an increase in the electrostatic attraction, in turn, facilitating the cation segregation and phase destruction of the electrodes.